APROXIMAÇÕES ENTRE O JORNALISMO CULTURAL E A RELIGIÃO: A ARTE E A CULTURA PELA PERSPECTIVA DO JORNAL BUDISTA BRASIL SEIKYO - BERTIN, CARLOS EDUARDO (2019)
This dissertation has the general purpose to understand how the newspaper Brazil Seikyo, belonging to the Brazilian Soka Gakkai International Association (BSGI), the Brazilian representative of the Soka Gakkai International (SGI), a non-governmental organization affiliated with the United Nations (UN), based on the Nichiren Daishonin Buddhism principles, addresses the art and culture themes in yours texts. The fact that this organization is inserted in the artistic and cultural field, through presentation groups and exhibitions and cultural activities, raised questions about how the newspaper deals with these two themes. Based on exploratory research and the precepts that guide BSGI, it was assumed that art and culture would be approached by the newspaper through the perspective of humanism and the culture of peace. The corpus of research was established from journalistic texts, based on the genres and formats of journalism, on art and culture published from 1999 to 2018. Bibliographical research, documentary research, interview with the editor-in-chief of the newspaper and content analysis were used as methodology. From inferences about the material, it was considered that the hypotheses are partially confirmed. It was noted that the informative texts are configured more by the institutional bias and give evidence to the instrumentalization of the artistic groups, expositions and cultural activities for the purposes of the BSGI’s peace culture and expansion of the Buddhist movement in Brazil. The opinion texts, on the other hand, demonstrate the approximation of the art and cultural products to the principles of Buddhism and BSGI, acting as mediator between the reader and these two specific themes.